Method for one-step solvothermal synthesis of ammonium fluoniobate powder
The high-purity and uniform morphology ammonium fluoroniobate powder was prepared by using niobium powder, hydrofluoric acid, acetic acid and urea raw materials by solvent-thermal method, which solved the problem of high preparation difficulty and low purity in the prior art, and achieved the Simplify preparation steps and broaden application potential.
Patent Information
- Application Number
- CN202411712897.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-18
AI Technical Summary
The difficulty in preparing ammonium fluoroniobate ((NH4)2Nb2O3F6) materials in the prior art lies in the difficulty of preparation, the low purity of the product, and the complex preparation steps.
Niobium powder, hydrofluoric acid, acetic acid and urea were used as raw materials to prepare (NH4)2Nb2O3F6 powder by a one-step solvothermal method. The method includes reacting niobium powder with hydrofluoric acid, adding acetic acid to adjust the pH of the reaction system, and forming a high-purity (NH4)2Nb2O3F6 powder by solvothermal reaction.
The preparation of (NH4)2Nb2O3F6 powder with high purity and uniform morphology has been achieved, the preparation steps are simplified, the raw material cost is reduced, and its application potential in the fields of catalysis, energy storage, etc. is expanded.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of micro-nano material preparation, and specifically relates to a process for preparing ammonium fluoroniobate ((NH4)2Nb2O3F6) powder by a solvent thermal method. Background Art
[0002] With the advancement of science and technology and the increasing demand for advanced functional materials, traditional single cation or anion compounds can no longer meet the development needs of modern applications. In order to enhance the performance of materials, researchers began to introduce additional cations into the compounds to give them new properties. For example, ferroelectric materials BaTiO3, yttria-zirconia (YSZ) for solid oxide fuel cells, and cathode materials Li for lithium batteries. x MnO2, etc., are all representatives of semiconductor materials with advanced functions. At the same time, in order to achieve more diversified material design, researchers have also begun to explore polyanionic compounds. This transformation is mainly reflected in the study of mixed anion materials such as fluoride oxides. Fluoride oxide research reveals the diversity of fluoride ions and oxygen ions in forming ordered or disordered patterns. For example, in lead-containing fluoride oxides, functional properties such as high dielectric constant and visible light catalysis are closely related to the arrangement of oxygen / fluoride ions. A. Demourgues et al. pointed out in the paper "Preparation and structural properties of new series of mixed-anion compounds: rare earthfluorosuldes" that the difference in polarizability of anions causes the structure to exhibit significant anisotropy, which may present two-dimensional or one-dimensional structural characteristics. The high polarizability, electronegativity and strong reactivity of fluoride ions can change the structural arrangement and charge density of cations, providing a theoretical and experimental basis for the design of new fluoride oxides.
[0003] In this context, ammonium fluoroniobate ((NH4)2Nb2O3F6), as a typical mixed anion-cation compound, has attracted extensive scientific research interest due to its unique crystal structure and potential excellent performance. This compound belongs to the Pnma space group and has an orthorhombic structure. In this crystal structure, Nb atoms are surrounded by six O or F atoms to form a Nb(O,F)6 octahedral structure. These octahedra are interconnected to form a double zigzag chain structure, and ammonium ions are located between the chains, showing its unique crystal geometry. However, there are few studies on the synthesis methods of (NH4)2Nb2O3F6, which limits its wide application in the field of advanced functional materials. In the paper "Reaction of niobium pentoxide withammonium hydrodifluoride", Tikhomirova et al. used niobium pentoxide and ammonium bifluoride as raw materials and successfully prepared (NH4)2Nb2O3F6 powder by heat treatment at 380℃ in air. In addition, this material can also be used as a precursor for the preparation of high-performance niobium-based oxide nanomaterials. Manickam Sasidharan et al. mentioned in the paper "Nb2O5 hollow nanospheres as anode material for enhanced performance in lithium ion batteries" that Nb2O5 nanomaterials can provide a high capacity of 172 mAh g as the negative electrode of lithium-ion batteries. And after 250 cycles, it maintains structural integrity and excellent cycle stability, and shows good high-rate performance. In addition, the high dielectric constant and other physical properties of Nb2O5 further broaden the potential application range of (NH4)2Nb2O3F6.
[0004] In order to overcome the difficulties in synthesizing (NH4)2Nb2O3F6, the present invention uses niobium powder, hydrofluoric acid, acetic acid and urea as raw materials, and prepares (NH4)2Nb2O3F6 powder with uniform morphology and high purity through a one-step solvothermal method. It has great application potential in the fields of photocatalysis and electrochemistry. This achievement marks an important progress in the field of materials science for polyanionic and cationic compounds, and opens up new possibilities for the design and application of high-performance materials in the future. Summary of the invention
[0005] The present invention is dedicated to solving the difficulties encountered in the process of preparing ammonium fluoroniobate ((NH4)2Nb2O3F6) material, such as high difficulty in preparation, low product purity and complicated preparation steps. To this end, the present invention proposes a solvothermal process, using metal niobium powder, hydrofluoric acid, acetic acid and urea as main raw materials, and preparing (NH4)2Nb2O3F6 material through the following detailed steps: (1) weighing metal niobium powder and 22.5mol / L hydrofluoric acid in a molar ratio of 1: (4-6). Dissolve the niobium powder in the hydrofluoric acid solution and stir evenly to prepare solution A. (2) Slowly add acetic acid to solution A, wherein the molar (mol): volume (L) ratio of metal niobium powder to 17.5mol / L acetic acid is 1: (1.5-3). Continue stirring until the mixture is evenly mixed to form solution B. (3) According to the molar ratio of metal niobium powder to urea of 1: (0.2~1), weigh urea and add it to solution B, continue stirring until it is completely mixed to form a mixed solution C. (4) Transfer solution C to the polytetrafluoroethylene liner of the reactor, and the filling degree reaches 30%~60%. Then, seal the reactor and transfer it to an oven, set the heating temperature to 160℃~200℃, and keep it warm for 5h~50h to carry out the solvothermal reaction. (5) After the reaction is completed, wait for the reactor to cool naturally to room temperature, separate the solid phase product by high-speed centrifugation, and wash it with deionized water several times to remove surface impurities. (6) After centrifugation, dry the solid phase product at 80℃ to obtain ammonium fluoroniobate ((NH4)2Nb2O3F6) powder.
[0006] The working principle of the present invention is based on the reaction of metal niobium (Nb) powder with hydrofluoric acid. By adding acetic acid, not only the pH of the reaction system is adjusted, but also the sedimentation rate of Nb ions is adjusted by forming an unstable niobium acetate complex, thereby accurately controlling the formation path of the product; and then (NH4)2Nb2O3F6 powder is formed in the solvent thermal reaction. The specific reaction process is as follows:
[0007] First, the metallic Nb powder reacts with excess HF acid to generate H2NbF7 and hydrogen (Equation (1)): 2Nb (s) +14HF (l) =2H2NbF 7(l) +5H 2(g) (1)
[0008] Where l represents liquid, s represents solid and g represents gas;
[0009] Then, acetic acid (CH3COOH) acts as a solvent in this solvothermal reaction, which has a moderate boiling point, good solubility and specific chemical properties. Acetic acid can not only adjust the pH value of the reaction system, but also react with niobium ions as a reaction medium (Equation (2)):
[0010] NbF-6 (l) + xCH3COOH (l) =[(CH3COO) x FWf 6-x ] - (l) +xHF (l) (2)
[0011] Under solvothermal conditions, the niobium acetate complex reacts with urea to form ((NH4)2(Nb x Ta 1-x )2O3F6) powder, the reaction equation is as follows:
[0012] 2[(CH3COO) x FWf 6-x ] - (l) + CO(NH2) 2(s) + 4H2O (l) +(2x-4)H + (l) = (NH4)2Nb2O3F 6(s) +2xCH3COOH (l) + (6-2x)F - (l) + CO 2(g) (3)
[0013] The advantages of the present invention are that the synthesized (NH4)2Nb2O3F6 powder has high purity and uniform morphology, and its preparation method is simple, the raw materials are easily available, and the preparation cycle is short. These characteristics make the present invention have important application value in multiple fields such as catalysis, energy storage, and as a precursor of niobium-based oxide nanomaterials. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is the XRD spectrum of the rod-shaped (NH4)2Nb2O3F6 material prepared in Example 1.
[0015] Figure 2 This is the SEM image of the rod-shaped (NH4)2Nb2O3F6 material prepared in Example 1.
[0016] Figure 3 This is the EDS spectrum of the rod-shaped (NH4)2Nb2O3F6 material prepared in Example 1.
[0017] Figure 4 This is the XRD spectrum of the rod-shaped (NH4)2Nb2O3F6 material prepared in Example 2.
[0018] Figure 5This is the SEM image of the rod-shaped (NH4)2Nb2O3F6 material prepared in Example 2.
[0019] Figure 6 This is the XRD spectrum of the rod-shaped (NH4)2Nb2O3F6 material prepared in Example 3.
[0020] Figure 7 This is the SEM image of the rod-shaped (NH4)2Nb2O3F6 material prepared in Example 3.
[0021] Figure 8 This is the EDS spectrum of the rod-shaped (NH4)2Nb2O3F6 material prepared in Example 3.
[0022] Fig. 9 This is the XRD spectrum of the rod-shaped (NH4)2Nb2O3F6 material prepared in Example 4.
[0023] Fig.10 This is the SEM image of the rod-shaped (NH4)2Nb2O3F6 material prepared in Example 4.
[0024] Fig.11 This is the XRD spectrum of the rod-shaped (NH4)2Nb2O3F6 material prepared in Example 5.
[0025] Fig.12 This is the XRD spectrum of the rod-shaped (NH4)2Nb2O3F6 material prepared in Example 6.
[0026] Fig.13 This is the SEM image of the rod-shaped (NH4)2Nb2O3F6 material prepared in Example 6. DETAILED DESCRIPTION
[0027] Embodiment 1:
[0028] (NH4)2Nb2O3F6 powder was prepared based on the solvothermal process, using niobium powder, hydrofluoric acid, analytical grade acetic acid and urea as raw materials. The following is the detailed operation process:
[0029] 1. First, weigh metal niobium powder and 22.5 mol / L hydrofluoric acid at a molar ratio of 1:5. Dissolve the niobium powder in the hydrofluoric acid solution and stir evenly to prepare solution A.
[0030] 2. According to the mole (mol): volume (L) ratio of metallic niobium powder to 17.5 mol / L analytical pure acetic acid of 1:2, weigh acetic acid and slowly add it dropwise to solution A. Continue stirring until uniform to obtain solution B.
[0031] 3. According to the molar ratio of niobium metal powder to urea of 1:0.5, weigh urea and add it to solution B, and continue to stir until uniform to form a mixed solution C.
[0032] 4. Transfer solution C to the polytetrafluoroethylene liner of the reactor, filling it to about 40%. Then seal the hydrothermal reactor and put it in an oven, set the heating temperature at 200°C, and keep it warm for 24 hours to carry out the solvent thermal reaction.
[0033] 5. After the reaction is completed, let the reactor cool naturally to room temperature and separate the solid phase product by high-speed centrifugation. Use deionized water to wash several times to remove surface impurities and ions.
[0034] 6. After centrifugation, the product was dried at 80°C to obtain (NH4)2Nb2O3F6 powder.
[0035] The prepared (NH4)2Nb2O3F6 powder was subjected to X-ray diffraction phase analysis (XRD), and its XRD spectrum is as follows: Figure 1 The results show that all XRD diffraction peaks match the standard card (JCPDS Card No.31-0070), and there are no other impurity diffraction peaks; the obtained XRD diffraction peaks are sharp, and its three strong diffraction peaks correspond to the corresponding crystal planes (004), (209), and (305) of the orthorhombic (NH4)2Nb2O3F6 phase; this shows that the prepared (NH4)2Nb2O3F6 powder has good crystallinity and high purity.
[0036] Figure 2 The scanning electron microscope (SEM) image of the prepared (NH4)2Nb2O3F6 material shows that the material has a rod-like structure with a length of 20~50μm. Some of the rod-like (NH4)2Nb2O3F6 show a tendency to grow in clusters (such as Figure 2 (as shown in (a)). Figure 2 (b) shows that the rod-shaped (NH4)2Nb2O3F6 material is composed of closely arranged units, showing a relatively dense appearance. Further, EDS point analysis was performed on it, and the spectrum obtained was as follows Figure 3 The presence of four elements, N, O, F and Nb, was confirmed. Combined with the XRD results, it was confirmed that the prepared product was (NH4)2Nb2O3F6 phase.
[0037] Embodiment 2:
[0038] (NH4)2Nb2O3F6 powder was prepared based on the solvothermal process, using niobium powder, hydrofluoric acid, analytical grade acetic acid and urea as raw materials. The following is the detailed operation process:
[0039] 1. First, weigh niobium metal powder and 22.5 mol / L hydrofluoric acid at a molar ratio of 1:5. Dissolve the niobium powder in the hydrofluoric acid solution and stir evenly to prepare solution A.
[0040] 2. According to the molar (mol): volume (L) ratio of metallic niobium powder to 17.5 mol / L acetic acid of 1:2, weigh acetic acid and slowly add it dropwise to solution A. Continue stirring until uniform to obtain solution B.
[0041] 3. According to the molar ratio of metallic niobium powder to urea of 1:0.5, weigh urea and add it to solution B, and continue to stir until uniform to form a mixed solution C.
[0042] 4. Transfer solution C to the polytetrafluoroethylene liner of the reactor, filling it to about 40%. Then seal the reactor and put it in an oven, set the heating temperature to 180℃, and keep it warm for 48 hours to carry out the solvent thermal reaction.
[0043] 5. After the reaction is completed, let the hydrothermal reactor cool naturally to room temperature and separate the solid phase product by high-speed centrifugation. Use deionized water to wash several times to remove surface impurities and ions.
[0044] 6. The solid product obtained after centrifugation was dried at 80°C to finally obtain (NH4)2Nb2O3F6 powder.
[0045] The prepared (NH4)2Nb2O3F6 powder was subjected to X-ray diffraction phase analysis (XRD), and the obtained XRD spectrum was as follows: Figure 4 The results show that all XRD diffraction peaks match the standard card (JCPDS Card No.31-0070), and there are no other impurity diffraction peaks; the obtained XRD diffraction peaks are sharp, and its three strong diffraction peaks correspond to the (004), (321) and (132) crystal planes of the orthorhombic (NH4)2Nb2O3F6 phase, respectively; this shows that the prepared (NH4)2Nb2O3F6 powder has good crystallinity and high purity.
[0046] Figure 5 The SEM image of the prepared (NH4)2Nb2O3F6 material shows that the product has a block structure with a length of 2~20μm, and some (NH4)2Nb2O3F6 show a tendency to grow in clusters (such as Figure 5 (as shown in (a)). Figure 5 (b) shows that the (NH4)2Nb2O3F6 material is composed of closely arranged units, showing a relatively dense appearance.
[0047] Embodiment 3:
[0048] (NH4)2Nb2O3F6 powder was prepared based on the solvothermal process, using niobium powder, hydrofluoric acid, analytical grade acetic acid and urea as raw materials. The following is the detailed operation process:
[0049] First, metal niobium powder and 22.5 mol / L hydrofluoric acid were weighed at a molar ratio of 1:5. The niobium powder was dissolved in the hydrofluoric acid solution and stirred evenly to prepare solution A.
[0050] According to the mole (mol): volume (L) ratio of metallic niobium powder to 17.5 mol / L analytical pure acetic acid of 1:2, weigh acetic acid and slowly add it dropwise to solution A. Continue stirring until uniform to obtain solution B.
[0051] According to the molar ratio of metal niobium powder to urea of 1:0.5, urea was weighed and added to solution B, and the mixture was stirred until uniform to form a mixed solution C.
[0052] Solution C was transferred to the polytetrafluoroethylene liner of the reactor with a filling degree of about 40%. The reactor was then sealed and placed in an oven with the heating temperature set at 180°C and the holding time set at 24 h for a solvothermal reaction.
[0053] After the reaction is completed, the reactor is allowed to cool naturally to room temperature, the product and the solution are separated by high-speed centrifugation, and the product is washed and centrifuged with deionized water for multiple times to make it neutral to remove surface impurities.
[0054] The product obtained after centrifugation was dried at 80°C to obtain (NH4)2Nb2O3F6 powder.
[0055] The prepared (NH4)2Nb2O3F6 powder was subjected to X-ray diffraction phase analysis (XRD), and its XRD spectrum is as follows: Figure 6 The results show that all XRD diffraction peaks match the standard card (JCPDS Card No.31-0070), and there are no other impurity diffraction peaks; the obtained XRD diffraction peaks are sharp, and its three strong diffraction peaks correspond to the (004), (223) and (209) crystal planes of the orthorhombic (NH4)2Nb2O3F6 phase, respectively; this shows that the prepared (NH4)2Nb2O3F6 material has good crystallinity and high purity.
[0056] Figure 7 The SEM image of the prepared (NH4)2Nb2O3F6 powder is shown in Figure 2. The results show that the product has a rod-like structure with a length of 20 to 80 μm. Some of the rod-like (NH4)2Nb2O3F6 show a tendency to grow in clusters (e.g. Figure 7 (as shown in (a)). Figure 7 (b) shows that the rod-like (NH4)2Nb2O3F6 material is composed of closely arranged units, showing a relatively dense appearance.
[0057] Further, the EDS point analysis was performed and the obtained spectrum was as follows Figure 8The presence of four elements, N, O, F and Nb, was confirmed. Combined with the XRD results, it was confirmed that the prepared product was (NH4)2Nb2O3F6 phase.
[0058] Embodiment 4:
[0059] (NH4)2Nb2O3F6 powder was prepared based on the solvothermal process, using niobium powder, hydrofluoric acid, analytical grade acetic acid and urea as raw materials. The following is the detailed operation process:
[0060] First, metal niobium powder and 22.5 mol / L hydrofluoric acid were weighed at a molar ratio of 1:5. The niobium powder was dissolved in the hydrofluoric acid solution and stirred evenly to prepare solution A.
[0061] According to the mole (mol): volume (L) ratio of metallic niobium powder to 17.5 mol / L analytically pure acetic acid of 1:2, weigh acetic acid and slowly drop it into solution A. Continue stirring until uniform to obtain solution B.
[0062] According to the molar ratio of metal niobium powder to urea of 1:0.5, urea was weighed and added to solution B, and the mixture was stirred until uniform to form a mixed solution C.
[0063] Solution C was transferred to the polytetrafluoroethylene liner of the reactor with a filling degree of about 40%. The reactor was then sealed and placed in an oven, and the heating temperature was set at 180°C for 12 hours to carry out a solvothermal reaction.
[0064] After the reaction is completed, the reactor is allowed to cool naturally to room temperature, and the solid phase product is separated by high-speed centrifugation. Deionized water is used for multiple washing to remove impurities and ions on the surface of the product.
[0065] The product obtained after centrifugation was dried at 80°C to finally obtain (NH4)2Nb2O3F6 powder.
[0066] The prepared black (NH4)2Nb2O3F6 powder was subjected to X-ray diffraction phase analysis (XRD), as shown in FIG. Fig. 9 The results show that all XRD diffraction peaks are consistent with the standard card (JCPDS Card No.31-0070), the diffraction peaks are sharp and there are no other impurity diffraction peaks; the three strong peaks correspond to the (321), (004) and (202) crystal planes of the orthorhombic (NH4)2Nb2O3F6 phase, respectively; it proves that the prepared (NH4)2Nb2O3F6 material has high crystallinity and high purity.
[0067] Fig.10The SEM image of the prepared (NH4)2Nb2O3F6 material shows that the product has a rod-like structure with a length of 20~60μm. Some of the rod-like (NH4)2Nb2O3F6 show a tendency to grow in clusters (such as Fig.10 (as shown in (a)). Fig.10 (b) shows that the rod-like (NH4)2Nb2O3F6 material is composed of closely arranged units, showing a relatively dense appearance.
[0068] Embodiment 5:
[0069] (NH4)2Nb2O3F6 powder was prepared by solvothermal process, using niobium powder, hydrofluoric acid, analytical grade acetic acid and urea as raw materials. The following is the detailed operation process:
[0070] First, metal niobium powder and 22.5 mol / L hydrofluoric acid were weighed at a molar ratio of 1:5. The niobium powder was dissolved in the hydrofluoric acid solution and stirred evenly to prepare solution A.
[0071] According to the mole (mol): volume (L) ratio of metallic niobium powder to 17.5 mol / L analytically pure acetic acid of 1:2, weigh acetic acid and slowly add it dropwise to solution A. Continue stirring until uniform to obtain solution B.
[0072] According to the molar ratio of metal niobium powder to urea of 1:0.5, urea was weighed and added to solution B, and the mixture was stirred until uniform to form a mixed solution C.
[0073] Solution C was transferred to the polytetrafluoroethylene liner of the reactor with a filling degree of about 40%. The reactor was then sealed and placed in an oven with the heating temperature set at 180°C for 6 hours to carry out a solvothermal reaction.
[0074] After the reaction is completed, the reactor is allowed to cool naturally to room temperature, and the solid phase product is separated by high-speed centrifugation. Deionized water is used for multiple washing to remove surface impurities and ions.
[0075] 6. After centrifugation, the product was dried at 80°C to obtain (NH4)2Nb2O3F6 powder.
[0076] The prepared (NH4)2Nb2O3F6 powder was subjected to X-ray diffraction phase analysis (XRD), as shown in FIG. Fig.11 The results show that all XRD diffraction peaks are consistent with the standard card (JCPDS Card No.31-0070), the diffraction peaks are sharp and there are no other impurity diffraction peaks; the three strong peaks correspond to the (132), (321) and (322) crystal planes of the orthorhombic (NH4)2Nb2O3F6 phase, respectively; it proves that the prepared (NH4)2Nb2O3F6 material is single-phase and has high crystallinity and high purity.
[0077] Embodiment 6:
[0078] (NH4)2Nb2O3F6 powder was prepared by solvothermal process, using niobium powder, hydrofluoric acid, analytical grade acetic acid and urea as raw materials. The following is the detailed operation process:
[0079] First, metal niobium powder and 22.5 mol / L hydrofluoric acid were weighed at a molar ratio of 1:5. The niobium powder was dissolved in the hydrofluoric acid solution and stirred evenly to prepare solution A.
[0080] According to the molar (mol): volume (L) ratio of metallic niobium powder to 17.5 mol / L analytically pure acetic acid of 1:2, weigh acetic acid and slowly add it dropwise to solution A. Continue stirring until uniform to obtain solution B.
[0081] According to the molar ratio of metal niobium powder to urea of 1:0.5, urea was weighed and added to solution B, and stirring was continued until uniform to form a mixed solution C.
[0082] Solution C was transferred to the polytetrafluoroethylene liner of the reactor with a filling degree of about 40%. The reactor was then sealed and placed in an oven with the heating temperature set at 160°C for 12 hours to carry out a solvothermal reaction.
[0083] After the reaction is completed, the reactor is allowed to cool naturally to room temperature, the solid phase product is separated by high-speed centrifugation, and washed with deionized water for multiple times to remove surface impurities and ions.
[0084] The product obtained after centrifugation was dried at 80°C to finally obtain (NH4)2Nb2O3F6 powder.
[0085] The prepared (NH4)2Nb2O3F6 powder was subjected to X-ray diffraction phase analysis (XRD), as shown in FIG. Fig.12 The results show that all XRD diffraction peaks are consistent with the standard card (JCPDS Card No.31-0070), the diffraction peaks are sharp and there are no other impurity diffraction peaks; the three strong peaks correspond to the (004), (321) and (209) crystal planes of the orthorhombic (NH4)2Nb2O3F6 phase, respectively; it proves that the prepared (NH4)2Nb2O3F6 material is single-phase and has high crystallinity and high purity.
[0086] Fig.13 The SEM image of the prepared (NH4)2Nb2O3F6 material shows that the product has a rod-like structure with a length of 15~100μm. Some of the rod-like (NH4)2Nb2O3F6 show a tendency to grow in clusters (such as Fig.13 (as shown in (a)). Fig.13(b) shows that the rod-like (NH4)2Nb2O3F6 material is composed of closely arranged units, showing a relatively dense appearance.
[0087] Embodiment 7:
[0088] (NH4)2Nb2O3F6 powder was prepared by solvothermal process, using niobium powder, hydrofluoric acid, analytical grade acetic acid and urea as raw materials. The following is the detailed operation process:
[0089] First, metal niobium powder and 22.5 mol / L hydrofluoric acid were weighed at a molar ratio of 1:4. The niobium powder was dissolved in the hydrofluoric acid solution and stirred evenly to obtain solution A.
[0090] According to the mole (mol): volume (L) ratio of metallic niobium powder to 17.5 mol / L analytically pure acetic acid of 1:1.5, weigh acetic acid and slowly drop it into solution A. Continue stirring until uniform to obtain solution B.
[0091] According to the molar ratio of metal niobium powder to urea of 1:0.2, urea was weighed and added to solution B, and the mixture was stirred until uniform to form a mixed solution C.
[0092] Solution C was transferred to the polytetrafluoroethylene liner of the reactor with a filling degree of about 30%. The reactor was then sealed and placed in an oven with the heating temperature set at 200°C for 5 hours to carry out a solvothermal reaction.
[0093] After the reaction is completed, the reactor is allowed to cool naturally to room temperature, the solid phase product is separated by high-speed centrifugation, and washed multiple times with deionized water to remove impurities and ions on the product surface.
[0094] 6. After centrifugation, the product was dried at 80°C to obtain (NH4)2Nb2O3F6 powder.
[0095] Embodiment 8:
[0096] (NH4)2Nb2O3F6 powder was prepared by solvothermal process, using niobium powder, hydrofluoric acid, analytical grade acetic acid and urea as raw materials. The following is the detailed operation process:
[0097] 1. First, weigh niobium metal powder and 22.5 mol / L hydrofluoric acid at a molar ratio of 1:6. Dissolve the niobium powder in the hydrofluoric acid solution and stir evenly to prepare solution A.
[0098] 2. According to the mole (mol): volume (L) ratio of metallic niobium powder to 17.5 mol / L analytically pure acetic acid of 1:3, weigh acetic acid and slowly add it dropwise to solution A. Continue stirring until uniform to obtain solution B.
[0099] 3. According to the molar ratio of niobium metal powder to urea of 1:1, weigh urea and add it to solution B, and continue to stir until uniform to form a mixed solution C.
[0100] 4. Transfer solution C to the polytetrafluoroethylene liner of the reactor, filling it to about 60%. Then seal the reactor and put it in an oven, set the heating temperature to 160℃, and keep it warm for 50 hours to carry out the solvent thermal reaction.
[0101] 5. After the reaction is completed, let the reactor cool naturally to room temperature, separate the solid phase product by high-speed centrifugation, and wash it with deionized water several times to remove impurities and ions on the product surface.
[0102] 6. After centrifugation, the product was dried at 80°C to obtain (NH4)2Nb2O3F6 powder.
Claims
1. A process for preparing ammonium fluoroniobate ((NH4)2Nb2O3F6) powder by a solvothermal method, characterized in that: Niobium powder, 22.5 mol / L hydrofluoric acid, analytical grade acetic acid, urea and deionized water are used as raw materials; the specific steps are as follows: (1) Accurately weigh the niobium powder and hydrofluoric acid in a molar ratio of 1: (4-6); Under magnetic stirring, completely dissolve the niobium powder in hydrofluoric acid to prepare solution A. (2) According to the molar (mol) and volume (L) ratio of niobium powder to analytical grade acetic acid of 1: (1.5-3), weigh acetic acid and slowly add it dropwise to solution A. Continue stirring until uniform to obtain solution B. (3) Accurately weigh urea according to the molar ratio of niobium powder to urea of 1: (0.2~1), add it to solution B, and continue to stir until it is uniform to form a mixed solution C; (4) Transfer solution C to the polytetrafluoroethylene liner of the reactor with a filling degree of 30%~60%; then seal the reactor and transfer it to an oven, set the heating temperature to 160℃~200℃ and keep it warm for 5h~50h to carry out a solvothermal reaction; (5) After the reaction, let the hydrothermal reactor cool naturally to room temperature, separate the solid phase product, and use deionized water to wash the product several times until it is neutral to remove surface impurities; (6) The solid phase product obtained after centrifugation is dried at 80°C to finally obtain ammonium fluoroniobate ((NH4)2Nb2O3F6) powder.